Nutritional Value of Some Local Mushroom Species of Nepal - Mishra, Akkal Deo; Mishra, Manju (Janapriya Journal of Interdisciplinary Studies, 2017)
A study on the nutrients of cultivated and wild mushrooms as a sample analysis is carried out. The variation of chemical constituents based on the species, substratum and season has been observed for three cultivated species namely Agaricus bisporus, Pleurotus sajorcaju and Laccaria leccata alongwith one wild species namely Laetiporus sulphureus. The observations have been made for saw dust, paddy straw and wheat straw as substratum. Saw dust is found to produce higher yield followed by paddy straw in summer season as compared to winter vegetation. On the average 1.5 kg of saw dust produced 1 kg of mushroom. Some principal nutrients like carbohydrates, amino acids, proteins, fats, minerals, fibre and ash, moisture content, etc. are estimated from the mentioned mushroom species. The maximum amount of nutrients contained in 100gm of dry mass is 90% moisture, 15% fibre and ash, 8% carbohydrates, 12% amino acids, 32% proteins and 2.5% fat contents among the mushroom species studied. These mushrooms possess considerable amount of minerals like sodium, potassium, calcium, iron, phosphorus, etc. The maximum amount of these mineral elements in the mushrooms under experiment is 5% sodium, 6% phosphorus, 4% potassium, 2.5% calcium and 3% iron in straw based vegetation grown in summer season. The mushroom species studied have been tested against different fungal and bacterial strains to observe their microbiological activities by using their biomass extract. They are found mild to moderate in antifungal and antibacterial activities. The wild species have shown higher potentiality against in vitro tested microbes as compared to cultivated mushrooms under experiment. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), Page: 1-11